2018
DOI: 10.1016/j.celrep.2018.01.053
|View full text |Cite
|
Sign up to set email alerts
|

Commonly Occurring Cell Subsets in High-Grade Serous Ovarian Tumors Identified by Single-Cell Mass Cytometry

Abstract: We have performed an in-depth single-cell phenotypic characterization of high-grade serous ovarian cancer (HGSOC) by multiparametric mass cytometry (CyTOF). Using a CyTOF antibody panel to interrogate features of HGSOC biology, combined with unsupervised computational analysis, we identified noteworthy cell types co-occurring across the tumors. In addition to a dominant cell subset, each tumor harbored rarer cell phenotypes. One such group co-expressed E-cadherin and vimentin (EV), suggesting their potential r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
122
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(125 citation statements)
references
References 69 publications
2
122
0
1
Order By: Relevance
“…Five fresh NSCLC adenocarcinoma samples were obtained immediately after patient resection under IRB approval and underwent immediate dissociation for single-cell suspension. For mass cytometry analysis, we used the antibody panel developed for our time-course analysis, augmented with antibodies to sort out immune (CD45 + ), endothelial (CD31 + ) and stromal fibroblast (FAP + ) populations 13 . With this, we were able to discriminate immune, endothelial and stromal cells from cells that were of varying levels of cytokeratins 7 and 8, while at the same time negative for CD45, CD31 and FAP ( Supplementary Fig.…”
Section: Projection Of Clinical Nsclc Samples Onto the Emt-met Stamp mentioning
confidence: 99%
See 1 more Smart Citation
“…Five fresh NSCLC adenocarcinoma samples were obtained immediately after patient resection under IRB approval and underwent immediate dissociation for single-cell suspension. For mass cytometry analysis, we used the antibody panel developed for our time-course analysis, augmented with antibodies to sort out immune (CD45 + ), endothelial (CD31 + ) and stromal fibroblast (FAP + ) populations 13 . With this, we were able to discriminate immune, endothelial and stromal cells from cells that were of varying levels of cytokeratins 7 and 8, while at the same time negative for CD45, CD31 and FAP ( Supplementary Fig.…”
Section: Projection Of Clinical Nsclc Samples Onto the Emt-met Stamp mentioning
confidence: 99%
“…Pastushenko et al demonstrated the existence of partial EMT states in mammary and skin cancer by examining a large number of surface markers with flow cytometry and sc-RNAseq 12 . Gonzalez et al identified partial EMT states in clinical ovarian cancer samples with mass cytometry 13 . While these studies provide important insights, they did not directly relate their findings to EMT states that have been well characterized in cell lines or preclinical reference in vitro models.…”
Section: Introductionmentioning
confidence: 99%
“…NMD inhibition triggers cell death through activation of the unfolded protein response. Recent studies of HGSOC with multiparametric mass spectrometry have identified rare cell phenotypes within ovarian tumors in addition to the dominant cell subset . Rare populations included ovarian cancer cells that coexpressed vimentin and E‐cadherin, which may play a role in epithelial mesenchymal transition, as well as populations that coexpressed vimentin, HE4, and c‐myc, which were associated with poor patient outcome.…”
Section: How Do We Measure and Target The Genetic Epigenetic And Trmentioning
confidence: 99%
“…CellCNN is another supervised analysis tool that requires prospective assignment of samples to categories and uses convolutional neural networks to learn a filter that predicts whether new cells match one of the groups 15 . Other cell subset discovery approaches do not supervise the analysis with knowledge of clinical outcomes but do use prior biological knowledge to identify cell subpopulations and then test whether differential outcomes are associated these cell subsets 5,6,16 . In mass cytometry analysis, another common approach is to use tools for automated, unsupervised cell discovery and characterization, including SPADE 17 , t-SNE 18 , UMAP 19 , FlowSOM 20 , and Marker Enrichment Modeling (MEM 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mass cytometry has recently been developed for human solid tumors 11,16,24,25 , including glioblastoma, the most common primary malignant brain tumor in adults 26 . The median survival of glioblastoma patients after diagnosis has remained approximately 12-15 months for over a decade 27,28 .…”
Section: Introductionmentioning
confidence: 99%